A Retrospective Survey of Patients Undergoing Maintenance Hemodialysis vis-à-vis Cancer Prevalence (Journal of Analytical Oncology, 2020)
The present study investigated the cancer prevalence and anticancer treatment patients undergoing hemodialysis at Nagoya Memorial Hospital. We retrospectively analyzed 663 patients undergoing hemodialysis between September 2014 and August 2019, including patient characteristics such as age, sex, and underlying diseases, cancer type, and cancer treatment. Seventy-eight patients (11.9%) of the dialysis population were diagnosed with cancer. Cancer type was then compared between registered cancer patients undergoing maintenance dialysis (N = 78) and non-dialysis controls (N = 3279) during the same period. Colorectal carcinoma is the most common malignancy diagnosed in our hospital, accounting for approximately 15% of all types of cancers. The data of anticancer treatment for this disease were compared between dialysis patients (N = 15) and controls (N = 563), whose clinical stages were defined according to the Japanese Classification of Colorectal, Appendiceal, and Anal Carcinoma. Since the need to administer chemotherapeutic agents to dialysis patients with colorectal carcinoma will increase, oncologists should collaborate with nephrologists to cautiously manage anticancer treatment to avoid severe toxicities.